Spatial Effect Analysis of Health Expenditure and Health Output in China From 2011 to 2018 - Penghui Xu; Penghui Xu; Xicang Zhao; Haili Li; Shi Guo (Frontiers Media S.A., 2022)
ObjectiveThe objective of this study is to study the spatial effects of health expenditure and health output in China.MethodsUsing the spatial panel data of 31 provinces in China from 2011 to 2018, the spatial weight matrix was introduced to analyze the spatial correlation, and the spatial Durbin model (SDM) was used to investigate the health output effect of health expenditure.ResultsExcluding the number of doctors per thousand, the provincial health expenditure, the number of beds per thousand population, and per capita education level had a positive impact on the regional health output. The health effect of China's health inputs showed a spatial spillover effect.ConclusionDue to the significant spatial effect, the health output of 31 provinces in China benefits not only from the local health inputs, but also from the health inputs of neighboring provinces.SuggestionsThis article puts forward some suggestions based on the conclusion: China should strengthen the health cooperation among neighboring provinces, promote the free flow of various health factors among provinces, make full use of the spillover and interdependence of health investment among provinces, and improve the medical policy environment in China.